Umbilical mucosal polyp in an infant: a rare entity Mimicking umbilical granuloma - Dr. Archana Shetty; Dr. Shubha H.V; Dr. Vijaya C.; Dr. Venkatachalapathy V (Tropical Journal of Pathology and Microbiology, 2018)
Umbilical lesions constitute a comparatively lesser percentage of the specimens received on a daily basis for histopathological examination. During embryological development, the umbilicus functions as a channel that allows flow of blood between the placenta and fetus. It also serves an important role in the development of the intestine and the urinary system. After birth, once the umbilical cord falls off, no evidence of these connections should be present. Nevertheless a few lesions are encountered related to the same. Patients with umbilical disorders present with drainage, a mass, or both. Umbilical granuloma, omphalomesenteric remnants, urachal remnants, hernias are few lesions in the umbilical region. We present a case of an umbilical polyp in an infant, which clinically suspected to an umbilical granuloma. The idea behind presenting this case was that, not only are umbilical polyps rare lesions but also it is necessary to differentiate it from umbilical granuloma as the treatments may vary. The clinicians and reporting pathologists must be aware of this rare congenital lesion.